Cultural DNA : the psychology of globalization - Bains, Gurnek (Hoboken, New Jersey : Wiley, 2015)
"Develop a deeper cultural intelligence to thrive in a globalized marketplaceCultural DNA is a manual for successful engagement with cultures around the world. Written by founder and chairman of a global business psychology consultancy, this book guides leaders through the essential globalization management soft skills required to remain relevant in an increasingly connected business world. Readers will learn about the psychological themes at play in the U.S., Latin America, Europe, China, India, The Middle East, and Sub-Saharan Africa, and study the quantitative analysis from an extensive database of leaders. Groundbreaking behavioral genetics research shows exactly how companies and leaders can excel, turning globalization into a major competitive advantage.Borders and boundaries are becoming increasingly irrelevant in business operations, and leaders are required to engage in other cultures more deeply than ever before. This global-cultural convergence has highlighted both similarities and deep-rooted differences, and it's up to the leaders involved in these exchanges to bridge the divide and pursue the goals that benefit both sides. Cultural DNA provides the information and insight that leads to these successes, helping readers to: Develop deeper empathy and respect for other cultures Appreciate difference and leverage it better for competitive advantage Anticipate cultural differences and solve issues before they arise Thoughtfully manage globalization-driven convergences to find a common ground Excel at managing globalization by applying cultural intelligence Successful leaders understand that in certain situations, it's the soft skills that matter most. Globalization demands that cultures learn to work within each other's needs and expectations, and the right mix of people skills, business acumen, and cultural awareness is key. For the global business leader, Cultural DNA is a handbook for successful exchange"--
Bounded Sociability and EmpathyThe Art of Copying; Future Considerations; Notes; Chapter 6: Europe: The Equal Society; The Forces that have Shaped European Cultural DNA; Equality and Elitism; Bounded Individualism; Analyisis and Structured Planning; Reserved Sociability; The Diminishing Drive for Mastery; The Opportunities and Challenges for European Culture; Notes; Chapter 7: The Far Continents; Latin America-The Ever-Changing Melting Pot; Australia: Mateship in a Far-Off Land; Notes; Conclusions; Index; End User License Agreement
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cultural intelligence; Leadership -- Psychological aspects; Career development; Culture and globalization; BUSINESS & ECONOMICS / Careers / General; Career development; Cultural intelligence; Culture and globalization; Leadership -- Psychological aspects; Electronic books; Electronic books